Phytochemical investigation of lepisanthes rubiginosa / Amir Aiman Mohammad Zaini - Mohammad Zaini, Amir Aiman (2013)
Lepisanthes is a member of the family Sapindaceae. The genus is distributed widely, from tropical Africa and Madagascar, to Southeast Asia and Australia. Lepisanthes rubiginosa is native to Malaysia and is usually used as traditional medicine. This plant has been selected for this study due to its supposed medicinal properties. There are very little studies have been conducted. The main objective of this study is to obtain good HPLC profiles of the methanolic extract of the bark of Lepisanthes rubiginosa. DAD and ELSD detectors were selected to detect both UV active and UV inactive compounds. ACN and water were chosen as mobile phase. Different HPLC methods were attempted. Good HPLC profiles were generated and it was discovered that the extract contains both UV active and UV inactive compounds.